2020
DOI: 10.15520/ijmhs.v10i10.3119
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge of Breast Cancer Risk Factors and Practices of Breast Self-Examination among Women in Northern Ghana

Abstract: Introduction: Breast cancer remains a major global health concern in both developed and developing countries. The current study aimed to assess the knowledge of risk factors of breast cancer (BC), and the practice of breast self-examination (BSE) among females in the Tamale Metropolis of Northern Ghana. Methods: This is a cross-sectional study involving 1122 participants; consisting of nurses 157 (14.1%), teachers 227 (20.2%), undergraduate university students 339 (30.5%), medical students 95 (8.5%) and market… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(9 citation statements)
references
References 26 publications
0
9
0
Order By: Relevance
“…Two of the studies were nationwide. Three studies [ 32 , 35 , 36 ] assessed women’s knowledge and practices on BSE, CBE, and mammography while six studies focused on only BSE [ 26 , 28 , 30 , 31 , 34 , 37 ]. Two studies focused on BSE and CBE [ 27 , 33 ] while one study focused on only mammography [ 29 ] (Table 1 ).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Two of the studies were nationwide. Three studies [ 32 , 35 , 36 ] assessed women’s knowledge and practices on BSE, CBE, and mammography while six studies focused on only BSE [ 26 , 28 , 30 , 31 , 34 , 37 ]. Two studies focused on BSE and CBE [ 27 , 33 ] while one study focused on only mammography [ 29 ] (Table 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…Among the 14 studies included, eight studies reported evidence on Ghanaian women’s knowledge of BCS practices [ 25 , 27 , 28 , 30 – 32 , 34 , 37 ]. Among the various types of BCS, women reported high knowledge of BSE.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations